Analysis on electrical characteristics of high-voltage GaN-based light-emitting diodes - 郭伟玲 闫薇薇 朱彦旭 刘建朋 丁艳 崔德胜 吴国庆 (Chinese physics B, 2012)
In order to investigate their electrical characteristics, high-voltage light-emitting-diodes （HV-LEDs） each contain- ing four cells in series are fabricated. The electrical parameters including varying voltage and parasitic effect are studied. It is shown that the ideality factors （IFs） of the HV-LEDs with different numbers of cells are 1.6, 3.4, 4.7, and 6.4. IF increases linearly with the number of cells increasing. Moreover, the performance of the HV-LED with failure cells is examined, The analysis indicates that the failure cell has a parallel resistance which induces the leakage of the failure cell. The series resistance of the failure cell is 76.8 Ω, while that of the normal cell is 21.3 Ω. The scanning electron microscope （SEM） image indicates that different metal layers do not contact well. It is hard to deposit the metal layers in the deep isolation trenches. The fabrication process of HV-LEDs needs to be optimized.